Mitochondrial mechanisms in autism spectrum disorder: characterizing the neurotoxic effects of propionic acid in vitro - Mahony, Caitlyn (Department of Molecular and Cell Biology, 2025)
Autism Spectrum Disorder (ASD) is a chronic neurodevelopmental condition with a complex molecular aetiology shaped by genetic, epigenetic and environmental factors. The poorly understood nature of ASD aetiology significantly impedes diagnosis and management of the condition, which substantially impairs quality of life. A role for mitochondrial dysfunction in ASD has become increasingly well-recognised, while mitochondria are also emerging as central regulators of neurodevelopment, physiology and function. Moreover, recent work in a South Africa (SA) ASD cohort reported differential DNA methylation (DNAm) signatures converging on mitochondrial metabolism and Propionyl CoA Carboxylase B (PCCB). This project aimed to better characterise the mitochondrial component of ASD aetiology using an in vitro system to mechanistically interrogate the molecular signatures found in an understudied SA population. Building on established preclinical models for both PCCB dysfunction and ASD, Propionic Acid (PPA) was used to recapitulate mitochondrial dysfunction in neuronal-like SH-SY5Y cells. The Thiazolyl Blue Tetrazolium Bromide (MTT), Luminescent ATP Detection and Tetramethylrhodamine, ethyl ester (TMRE) assays revealed a dose- and time-dependent decrease in cell viability from 4 to 72 hours, catalysed by an acute loss of mitochondrial membrane potential at 4 hours. In conjunction, reverse transcription quantitative polymerase chain reaction (RT-qPCR) assays showed an acute and sustained suppression of PCCB expression and a systemic dysregulation of the genes that govern mitochondrial metabolism (PGC1α, c-MYC), biogenesis (TFAM, NRF1), fission (DRP1) and fusion (STOML2, MFN1/2, OPA1). Confocal microscopy demonstrated associated disruptions to mitochondrial network morphology and integrity, characterised by decreased mitochondrial volume, increased mitochondrial fragmentation and perturbations to mitophagic flux. Finally, live-cell respirometry illustrated functional impairments to metabolic state marked by significant deficits in both oxidative and glycolytic ATP production. Having effectively recapitulated mitochondrial dysfunction in vitro, a model for neurogenesis was developed to examine the interplay between neuronal metabolism and maturation. Phase contrast microscopy, immunocytochemistry and respirometry assays confirmed the efficacy of differentiation, demonstrating successful cell cycle exit, efficient neurite production, elongation and branching, an increased β-III-tubulin (β3T): Nestin (NES) ratio and enhanced mitochondrial capacity. This system was harnessed to characterise PPA-induced disruptions to neurogenesis, demonstrating gross morphological aberrations and significant changes to the composition and connectivity of neuronal networks. Complementary image analysis workflows showed that PPA reduced the length and complexity of neurite processes, disrupted the localisation and expression of cytoskeletal markers and decreased the β3T:NES ratio, indicating substantial impairments to neuronal morphology and maturation. Lastly, global RNA sequencing was used to characterise the molecular mechanisms that disrupt neuronal maturation under PPA stress, revealing transcriptional signatures of developmental delay and neurotoxicity. PPA upregulated processes involved in pluripotency, proliferation and glycolysis, impaired epigenetic and metabolic reprogramming and inhibited synaptogenesis and neurotransmission. An interplay between stress-responsive, metabolic and neurogenic signalling emerged at the centre of the PPA transcriptome, highlighting reciprocal mechanisms that modulate substrate utilisation, differentiation, synaptogenesis and survival. Moreover, PPA systemically altered convergent mechanisms that shape extracellular matrix dynamics, leading to signatures of neuronal injury, apoptosis and excitotoxicity. Together, transcriptomic profiles reflected impairments to neurogenesis under PPA stress, driven by disruptions to the intrinsic and extrinsic landscapes that shape neuronal cell fate. This project established an in vitro model for neurogenesis and developmental neurotoxicity that lays the groundwork for mechanistic studies on neurodevelopment and disease. The work presented here provides a quantitative assessment of mitochondrial morphology, dynamics and function under PPA stress and is the first study to functionally demonstrate that PPA alters neuronal metabolism and differentiation in the SH-SY5Y model. Moreover, the transcriptional signatures of PPA exposure highlight novel processes that function at the interface between metabolism, neurodevelopment and neurotoxicity. Ultimately, these insights contribute to a mechanistic understanding of the mitochondrial component of ASD aetiology, which could inform the development of novel biomarkers and therapeutic strategies to improve long-term clinical outcomes.